PENGARUH INVESTMENT OPPORTUNITY SET, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, RETURN ON ASSET DAN SIZE TERHADAP NILAI PERUSAHAAN - Muhammad Sholihin, 07.3503.0701; Kartika, Andi (Students' Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of investment opportunity set, capital structure, the company's growth, return on assets and the size of the company values at Manufacturing Company Year period 2013-2015. The population in this research is manufacturing companies listed on the Stock Exchange during the years 2013-2015. The sample in this study as many as 66 companies. The sampling technique used purposive sampling. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: Investment opportunity set, the company's growth and return on assets and a significant positive effect on firm value. Capital structure and size of the company does not significantly influence the value of the company.Keywords: Investment Opportunity Set, Capital Structure, The Company's Growth, Return On Assets, Size and Value of The Company